The Influence of the Popularity of Romantic Films on TikTok on Generation Z's Interest in Watching Local Films - Zikri Fachrul Nurhadi; Hatri Sahara (Indonesian Scientific Publication, 2026)
The key issue in this study is the increasing dependence of Generation Z on TikTok as a primary source of entertainment, potentially replacing conventional film promotional media. Therefore, without adequate understanding, the local film industry risks failing to capitalize on TikTok's popularity strategically and sustainably. This topic is relevant, as local films face challenges in attracting young audiences. This study employed employed an exploratory quantitative approach with a sample of 30 active Generation Z TikTok users aged 19-25 years. Data were collected using a questionnaire with validity and reliability tests, classical assumption tests, and simple linear regression analysis. The results showed that film popularity on TikTok had a positive and significant influence on adolescents' viewing interest (0.647; p < 0,001) with an R² of 0.538, indicating that 53.8% of the variation in viewing interest was explained by popular films. The results show a relationship between the intensity of user interaction with film content on TikTok and the tendency to be interested in watching local films, with the involvement of film producers maximizing social media as an interactive promotional tool that can expand audience reach and increase awareness of local films. In this study, the popularity of romantic films was measured based on the level of exposure (frequency of watching film content) and engagement (interactions in the form of likes, comments, shares, and use of hashtags). The uniqueness of this study lies in its positioning of TikTok as an algorithmic and participatory communication space that shapes Generation Z's perceptions of local films.